Dossier : Place aux objets ! Présentification et vie des artefacts en Grèce ancienne (Mètis, 2018)
Issue: How can we break the paradigm in which objects are thought of as simple devices or mediators, ontologically distinct from human subjects? A close dialogue with anthropological fieldwork invites to focus on the « presence » of artifacts, as they are given within a « world horizon » (Merleau-Ponty). This report explores the phenomena, devices and contexts able to bring an artifact to life, paying close attention to their modes of presentification. Examining how they are activated sheds new light on the way objects are handled. What happens when an artifact is augmented, modified, hidden or, per contra, disclosed? What enunciative and visual strategies does it appear with? In that perspective, the artifact is not to be thought of as a closed, finite object, but has to be connected with the sensory environment it creates or which affects it.